EFFETTI DELLA RAGIONE. LA RAGIONE CRITICA DI ADORNO E FOUCAULT - Berni, Stefano (Daimon Revista Internacional de Filosofia, 1995)
During last years of his life Foucault recognized to work around the problems heredited by Nietzsche and Adorno.The essay wnts to demonstrate by working some «key-words», such as reason, ethics and freedom, the continuity and discontinuity of Foucault's thought in relationship to Adorno's.